Evaluacion de tres tipos de abonos orgánicos a tres dosis en el comportamiento agronómico de Arveja (pisum sativum) en terrazas de banco, CEYPSA-UTC, provincia de Cotopaxi, 2021. - Yungan Rumipamba, Jairo David (2021)
This research was carried out at the Technical University of Cotopaxi, in the CEASA experimental campus, at an altitude of 2765 meters above sea level, between the Montes of April / August 2021 on the bank terraces. It has an alkaline soil with a pH of 9.47, with a very low percentage of organic matter of 0.7%. The work consisted of evaluating the three types of organic fertilizers, eco bonaza, guinea pig fertilizer and humus, at three doses: 20 ton / ha, 15 ton / ha, 10 ton / Ha; a control (without fertilization), in the agronomic behavior of pea (pisum sativum), in bank terraces. A randomized complete block design was used with a factorial arrangement of 3 x 3 + 1, giving a total of 10 treatments and 30 experimental units. Using the analysis of variance to determine the statistical significance between the treatments and the Tukey test at 5% to determine the differences between means of the treatments. The research expressed the following results: in the germination percentage, the organic amendment based on Humus with its three application rates 10, 15, 20 tons / ha obtained the best average with 100% of germinated seeds in the period of 19 days after sowing. In the variable plant height, the guinea pig fertilizer with 20 and 15 tons / ha had a positive influence, with an average of 54.33 cm in length, surpassing the other fertilizers used. The EcoAbonaza fertilizer obtained the first place in the first flowering with its three doses applied (10, 15.20 ton / ha), with an average of 34, 33.33 of flowers. When talking about factor A (organic fertilizers) and factor B (dose), the humus-based amendment managed to be the best organic source in its three applied doses (10, 15,20 ton / ha) with an average of 50, 48, 36 nodular units, where there is statistical significance, due to the application of the organic amendment and its high nutritional content. Organic fertilizers constitute a crucial element for the regulation of many processes related to agricultural productivity. (Araus Ortega et al., 2003)